Comparison of genetically modified insect-resistant maize and non-transgenic maize revealed changes in soil metabolomes but not in rhizosphere bacterial community. Issue 1 (31st December 2022) - Chen, Yanjun; Pan, Libo; Ren, Mengyun; Li, Junsheng; Guan, Xiao; Tao, Jun
ABSTRACT: The deliberate introduction of the beneficial gene in crop plants through transgenic technology can provide enormous agricultural and economic benefits. However, the impact of commercialization of these crops on the ecosystem particularly on belowground soil biodiversity is still uncertain. Here, we examined and compared the effects of a non-transgenic maize cultivar and an insect-resistant transgenic maize cultivar genetically engineered with cry1Ah gene from Bacillus thuringiensis, on the rhizosphere bacterial community using 16S rDNA amplicon sequencing and soil metabolome profile using UPLC/MS analysis at six different growth stages. We found no significant differences in bacterial community composition and diversity at all growth stages between the two cultivars. The analysis of bacterial beta-diversity showed an evident difference in community structure attributed to plant different growth stages but not to the plant type. In contrast, the soil metabolic profile of transgenic maize differed from that of the non-transgenic plant at some growth stages, and most of the altered metabolites were usually related to the metabolism but not to the plant-microbe interaction related pathways. These results suggest that genetic modification with the cry1Ah gene-altered maize soil metabolism but had no obvious effect on the rhizosphere bacterial community.